Development of the Riverkeeper Game Using Canva Application to Teach Ecosystem Topic to High School Students (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
Ecosystem learning in secondary education often relies on theoretical instruction with minimal contextual engagement, leading to persistent misconceptions and low student understanding. This study aims to address this pedagogical gap by developing the Riverkeeper game, an innovative hybrid learning media that combines digital platforms (Canva, Wordwall, and Google Docs) with field exploration activities to support ecosystem instruction. Using a modified 4D development model (Define, Design, Develop, Disseminate) but only Define, Design and Develop stages were conducted in this paper. Data were collected from five biology teachers and twenty Grade 11 students to identify instructional challenges and needs. The Riverkeeper game was designed based on constructivist and experiential learning principles, integrating digital problem-solving tasks with real-world observation of river ecosystems. The media prototype underwent expert validation involving three evaluators (a biology education lecturer, a media expert, and a senior high school biology teacher) using a structured instrument covering three aspects: game guidance, visual communication and design, and functionality. Validation results showed an overall score of 88% (very valid), with strengths in instructional clarity and visual design, though minor revisions were suggested for navigation and technical integration. A practicality test involving twenty students reported high satisfaction and relevance to learning objectives. As this study focused solely on the development and validation stages, further research is recommended to evaluate the game’s effectiveness in improving student learning outcomes. The Riverkeeper game presents a novel approach to ecosystem education by integrating digital game-based learning with direct environmental exploration.